Fine Structure of Sporulation in Bacillus cereus Grown in a Chemically Defined Medium - Ellar, D. J. (1966)
Ellar, D. J. (Syracuse University, Syracuse, N.Y.), and D. G. Lundgren. Fine structure of sporulation in Bacillus cereus grown in a chemically defined medium. J. Bacteriol. 92:1748–1764. 1966.—A study was made of the fine structure of sporulating cells of Bacillus cereus grown in a chemically defined medium. The developmental stages of sporulation occurred in a fairly synchronous manner and were complete by 14 hr. This time period was shortened when spore wall peptide components were added to the medium, but the addition had no effect upon fine structure except to thicken the cell wall. Sporulation could be separated into six morphological stages which generally agreed with those published for other sporulating bacteria. The initiation of the spore (forespore) septum takes the form of an inward folding of the cytoplasmic membrane toward the pole of the cell. The inward folding forms a characteristic Y-shaped membrane structure enclosing an area within which vesicles are found. These vesicles comprise the perisporal mesosome of the cell. The membranes on opposite sides of the cell progress toward the cell center where they fuse to form the double unit membrane of the spore septum. As the proliferation of the spore septum continues, the vesicular areas move towards the pole. The end result is a double forespore membrane which completely encloses a part of the vegetative cell's chromatin. Sporal mesosomes, as well as membrane vesicles, are involved in the proliferation of the forespore. Vesicles are generally bounded by a single unit membrane, whereas in the sporal mesosomes several unit membranes are arranged concentrically. The latter become associated with the segregation of a portion of the nuclear material into the forespore region of the cell.